Sumienie i rozum praktyczny u Immanuela Kanta - Ricken, Friedrich (Horyzonty Wychowania, 2017)
Conscience is a court of second instance. It is practical mindinsofar as practical mind confronts us with the duty to judge ouractions and insofar as practical mind examines whether we havefulfilled this second order duty. Conscience allows an action onlyif practical mind is certain that the action is not wrong, and itexamines whether this claim has been fulfilled. Practical mindjudges the action; conscience convicts and sentences, or acquits.Practical mind is not able to decide the quaestio facti whetherI am responsible for the action; that is the task of conscience.The sanctions of conscience are moral feelings; it is only throughmoral feelings that we become aware of the necessity to judgeour actions through practical mind.